siRNAs induce efficient RNAi response in Bombyx mori embryos. - Junichi Yamaguchi; Takayuki Mizoguchi; Haruhiko Fujiwara (PLoS ONE, 2011)
Short interference RNA (siRNA) is widely used in mammalian cells. In insects, however, reports concerning the suitablility of siRNA in vivo is very limited compared with that of long dsRNA, which is thought to be more effective. There is insufficient information on the essential rules of siRNA design in insects, as very few siRNAs have been tested in this context. To establish an effective method of gene silencing using siRNA in vivo in insects, we determined the effects of siRNA on seven target genes. We designed siRNAs according to a new guideline and injected them into eggs of Bombyx mori. At the mRNA level, the expression of most of these genes was successfully silenced, down to less than half the constitutive level, which in some cases led to the development of distinctive phenotypes. In addition, we observed stronger effect of siRNA both on the mRNA level and the phenotype than that of long dsRNA under comparable conditions. These results indicate that direct injection of siRNA is an effective reverse-genetics tool for the analysis of embryogenesis in vivo in insects.